2009
DOI: 10.1538/expanim.58.67
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nanpao, a Kampo Medicine, on Peripheral Blood Flow and Surface Skin Temperature in Aged Female Rats

Abstract: Abstract:The effects of long-term treatment with Nanpao, a kampo medicine, on cold constitution were evaluated in aged female rats. Five-month-old rats were administered Nanpao orally at doses of 0, 30, or 100 mg/kg/day. The peripheral blood flow and surface skin temperature in the hind paws were measured using a laser Doppler blood flow meter and infrared thermography, respectively. In animals treated with Nanpao, the peripheral blood flow increased dose-dependently compared to that in the control group. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…These results indicate that a short period of administration of Nanpao prevented the age-related loss of regular estrous cycles [9]. Although the mechanism of the effect of Nanpao on the decline in reproductive function in female animals was not clear in the present study, we previously reported that Nanpao has the potential to improve peripheral blood flow and subsequently surface skin temperature [10]. Taking account of these findings, the inhibitory effect of the test drug on the decline in estrous cyclicity may be due to increased blood flow volume in the uterus and ovaries maintaining the normal environment of the uterus and ovaries and preventing the aging of the ovum.…”
Section: Discussionmentioning
confidence: 49%
“…These results indicate that a short period of administration of Nanpao prevented the age-related loss of regular estrous cycles [9]. Although the mechanism of the effect of Nanpao on the decline in reproductive function in female animals was not clear in the present study, we previously reported that Nanpao has the potential to improve peripheral blood flow and subsequently surface skin temperature [10]. Taking account of these findings, the inhibitory effect of the test drug on the decline in estrous cyclicity may be due to increased blood flow volume in the uterus and ovaries maintaining the normal environment of the uterus and ovaries and preventing the aging of the ovum.…”
Section: Discussionmentioning
confidence: 49%